(untitled) (ENTHYMEMA, 2011)
Review of Daniil Charms. Sobranije sočinenij v dvuch tomach [Collection of Works in two volumes]. ed. by Vladimir Vesterman. Moskva: AST and Zebra E, 2010; Daniil Charms. Sobranije sočinenij v trëch tomach [Collection of Works in three volumes]. ed. by Valerij Sažin, Sankt-Peterburg: Azbuka, 2011; Aleksandr Vvedenskij,Vsë [Everything]. ed. by Anna Gerasimova. OGI: Moskva, 2010.